The Dipeptide Monoester Prodrugs of Floxuridine and Gemcitabine-Feasibility of Orally Administrable Nucleoside Analogs - Yasuhiro Tsume; Blanca Borras Bermejo; Gordon L. Amidon (MDPI AG, 2014)
Dipeptide monoester prodrugs of floxuridine and gemcitabine were synthesized. Their chemical stability in buffers, enzymatic stability in cell homogenates, permeability in mouse intestinal membrane along with drug concentration in mouse plasma, and anti-proliferative activity in cancer cells were determined and compared to their parent drugs. Floxuridine prodrug was more enzymatically stable than floxuridine and the degradation from prodrug to parent drug works as the rate-limiting step. On the other hand, gemcitabine prodrug was less enzymatically stable than gemcitabine. Those dipeptide monoester prodrugs exhibited 2.4- to 48.7-fold higher uptake than their parent drugs in Caco-2, Panc-1, and AsPC-1 cells. Floxuridine and gemcitabine prodrugs showed superior permeability in mouse jejunum to their parent drugs and exhibited the higher drug concentration in plasma after in situ mouse perfusion. Cell proliferation assays in ductal pancreatic cancer cells, AsPC-1 and Panc-1, indicated that dipeptide prodrugs of floxuridine and gemcitabine were more potent than their parent drugs. The enhanced potency of nucleoside analogs was attributed to their improved membrane permeability. The prodrug forms of 5¢-L-phenylalanyl-l-tyrosyl-floxuridine and 5¢-L-phenylalanyl-L-tyrosyl-gemcitabine appeared in mouse plasma after the permeation of intestinal membrane and the first-pass effect, suggesting their potential for the development of oral dosage form for anti-cancer agents.